Quartz-Tuning-Fork-Enhanced Spectroscopy Based on Fast Fourier Transform Algorithm - Yang, Guangxiang; Xu, Linguang; Liang, Hua; Li, Jingsong (Frontiers in Physics, 2020)
In this paper, a gas sensing technique based on quartz-crystal-tuning-fork-enhanced spectroscopy (QCTFES) and wavelength modulation spectroscopy (WMS) is reported. To explore the capabilities of this technique, a near-infrared (NIR) diode laser emitting at 1,653 nm and a QCTF-based photoelectric detector are developed for measuring trace methane (CH4). For signal processing, a fast and effective signal analysis method based on the fast Fourier transform (FFT) algorithm is proposed for extracting the absorption intensity signal of the QCTFES-WMS, instead of a lock-in amplifier used for harmonic signal demodulation in traditional QCTF-based detection techniques. Primary laboratory results indicate that an excellent linearity response of CH4 concentration and optical power levels are founded, and a detection limit of 64 ppm is achieved with a 1-s averaging time, which can be further improved to 9 ppm at an optimal integral time of 250 s. Improvements in sensitivity and detectivity can be significantly achieved by using laser sources with higher output power. Compared to traditional WMS technique-based semiconductor photodetectors, the room-temperature QCTF-based WMS shows significant advantages of super-broadband wavelength response, much cheap and tiny.